PENERAPAN PEMBELAJARAN KOOPERATIF MODEL MIND MAPPING UNTUK MENINGKATKAN HASIL BELAJAR SISWA SDN 1 LANDUNGSARI DI MASA PANDEMI COVID-19 - M. Farid Nurul Anwar; Ika Widayanti (Program Studi PGSD, FKIP, Universitas Mataram, 2021)
The learning outcomes of class VIB SDN Landungsari 1 student did not reach the specified Minimum Completeness Criteria (MCC). Apart from the effects of the post-covid-19 pandemic, the cause of the low student learning scores was the learning model. The learning model must be following the times. One of the learning models is the mind mapping model of cooperative learning which is an innovative learning model. The purpose of this study was to describe the application of the mind mapping model of cooperative learning to improve student learning outcomes. This research was conducted in 2 cycles using the class action research method (CAR) with steps were action planning, action implementation, evaluation, and reflection in each cycle. The learning outcomes of cycle 1 showed the mean of affective, psychomotor, and cognitive values were 79.80, 62.50, and 73.84, respectively. The learning outcomes of cycle 2 showed an increase compared to the learning outcomes in preliminary observation and cycle 1 with the average values ​​of affective, psychomotor, and cognitive were 98, 93.75, and 86.92, respectively. The results of this study indicated that the mind mapping model of cooperative learning could improve student learning outcomes.